The Control of reflectance and Transmittance of glass using External Magnetic Field and Sound Waves Through Electrical Permittivity - Elharam Ali Eltahir; Faten Adel Mohammed (Taez University, 2023)
Optical properties of matter are important in solar cells and smart windows design. The properties like reflection and transmition are very important in these applications. Therefore, this work is concerned with studying these properties using Maxwell's equations. Using the expression of reflection and transmition coefficient useful relations were found. It was found that complete transmittance occurs when one applies a strong magnetic field. While applying an appropriate magnetic field leads to complete reflection and generation of amplified light in a direction normal to the incident one. Also, the thermal radiation can be reflected completely by applying sound wave having a certain frequency.